Epigenetic reprogramming in cancer: From diagnosis to treatment - Costa, Pedro Mikael da Silva; Sales, Sarah Leyenne Alves; Pinheiro, Daniel Pascoalino; Pontes, Larissa Queiroz; Maranhão, Sarah Sant’Anna; Pessoa, Claudia do Ó.; Furtado, Gilvan Pessoa; Furtado, Cristiana Libardi Miranda (Frontiers in Cell and Developmental Biology, 2023)
Disruption of the epigenetic program of gene expression is a hallmark of cancer that initiates and propagates tumorigenesis. Altered DNA methylation, histone modifications and ncRNAs expression are a feature of cancer cells. The dynamic epigenetic changes during oncogenic transformation are related to tumor heterogeneity, unlimited self-renewal and multi-lineage differentiation. This stem cell-like state or the aberrant reprogramming of cancer stem cells is the major challenge in treatment and drug resistance. Given the reversible nature of epigenetic modifications, the ability to restore the cancer epigenome through the inhibition of the epigenetic modifiers is a promising therapy for cancer treatment, either as a monotherapy or in combination with other anticancer therapies, including immunotherapies. Herein, we highlighted the main epigenetic alterations, their potential as a biomarker for early diagnosis and the epigenetic therapies approved for cancer treatment.